Predictive Physiological Modeling of Percutaneous Coronary Intervention – Is Virtual Treatment Planning the Future? - Gosling, Rebecca C.; Morris, Paul D.; Lawford, Patricia V.; Hose, D. Rodney; Gunn, Julian P. (Frontiers in Physiology, 2018)
Computational modelling has been used routinely in the pre-clinical development of medical devices such as coronary artery stents. The ability to simulate and predict physiological and structural parameters such as flow disturbance, wall shear-stress and mechanical strain patterns is beneficial to stent manufacturers. These methods are now emerging as useful clinical tools, used by physicians in the assessment and management of patients. Computational models which can predict the physiological response to intervention offer clinicians the ability to evaluate a number of different treatment strategies in silico prior to treating the patient in the cardiac catheter laboratory. For the first time clinicians can perform a patient-specific assessment prior to making treatment decisions. This could be advantageous in patients with complex disease patterns where the optimal treatment strategy is not clear. This article reviews the key advances and the potential barriers to clinical adoption and translation of these virtual treatment planning models.